Berberine prevents primary peritoneal adhesion and adhesion reformation by directly inhibiting TIMP-1 - Xin Liu; Yunwei Wei; Xue Bai; Mingqi Li; Huimin Li; Lei Wang; Shuqian Zhang; Xia Li; Tong Zhao; Yang Liu; Rui Geng; Hao Cui; et al. (Elsevier, 2020)
Peritoneal adhesions are fibrous tissues that tether organs to one another or to the peritoneal wall and represent the major cause of postsurgical morbidity. Enterolysis at repeat surgeries induces adhesion reformation that is more difficult to prevent than primary adhesion. Here we studied the preventive effects of different approaches of berberine treatment for primary adhesion, and its effects on adhesion reformation compared to Interceed. We found the primary adhesion was remarkably prevented by berberine through intraperitoneal injection 30 min before abrasive surgery (pre-berberine) or direct addition into injured cecum immediately after the surgery (inter-berberine). Rats with adhesion reformation had a more deteriorative collagen accumulation and tissue injury in abrasive sites than rats with primary adhesion. The dysregulated TIMP-1/MMP balance was observed in patients after surgery, as well as adhesion tissues from primary adhesion or adhesion reformation rats. Inter-berberine treatment had a better effect for adhesion reformation prevention than Interceed. Berberine promoted the activation of MMP-3 and MMP-8 by directly blocking TIMP-1 activation core, which was reversed by TIMP-1 overexpression in fibroblasts. In conclusion, this study suggests berberine as a reasonable approach for preventing primary adhesion formation and adhesion reformation.